(3eSGYOGJ GdJOQjH hEOGQI YedjGJ GdTQWI GdeJNUUI (B=s Training aids and specialized police operation management and police study : an applied study - (3YHO GdeWdH, eeOhM YHO GdMejO,s 1955- ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3GdbjGOI GdYGeI dTQWI GdTGQbI, eQcR GdHMhK hGdOQGSGJs, 1999)
(3jJfGhd cJGH (B((3eSGYOGJ GdJOQjH hEOGQI YedjGJ GdTQWI GdeJNUUI(B) (3hGdPj bGe HJCdjag (B((3eeOhM YHO GdMejO YHO GdeWdH(B) (3aj MhGdj (B(131) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3EOGQI TDhf GdehXajf GdTQWI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3eGgjI eSGYOGJ GdJOQjH hCfhGYgG, GdJYQja HeSGYOGJ GdJOQjH hfTCJgG hJWhQgG, CfhGY eSGYOGJ GdJOQjH GdJbfjI, eSGYOGJ GdJOQjH GdJbfjI, GdfeGPL GdJbfjI GdeNJdaI hOhQgG aj GdJOQjH, ZQaI GdYedjGJ cfehPL Jbfj ddJOQjH Ydi EOGQI GdYedjGJ GdTQWjI, bjGS CKQ GdJOQjH HGSJNOGe eSGYOGJ GdJOQjH GdJbfjI, GdeaGgje GdYGeI ddCOGA GdTQWI, CKQ eSGYOGJ GdJOQjH GdJbfjI Ydi JOQjH EOGQI YedjGJ GdTQWI(B.s
(3HHdjhLQGajI (B: (3UaMI (B130-131.s
Keywords: (3GdTQWIs -- (3EOGQI TDhf GdehXajfs; (3QLGd GdTQWIs -- (3JOQjHs -- (3GdEeGQGJ GdYQHjI GdeJMOIs